Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004201.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary catheter policies for long-term bladder drainage

Abstract: No eligible trials were identified that compared alternative routes of catheter insertion. The data from seven trials comparing differing antibiotic policies were sparse, particularly when intermittent catheterisation was considered separately from in-dwelling catheterisation. Possible benefits of antibiotic prophylaxis must be balanced against possible adverse effects, such as development of antibiotic resistant bacteria; these cannot be reliably estimated from currently available trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 31 publications
0
47
0
4
Order By: Relevance
“…Therefore it is not recommended (B). For patients using permanent urethral catheterisation, no data are available [80].…”
Section: Catheter Carementioning
confidence: 99%
“…Therefore it is not recommended (B). For patients using permanent urethral catheterisation, no data are available [80].…”
Section: Catheter Carementioning
confidence: 99%
“…Two meta-analyses combined results of 23 studies on the use of antibiotic prophylaxis for theprevention of UTIs in SCI patients and all are based on continual administration of a singleantibiotic [5,6]. The authors concluded that the potential benefits of antibiotic prophylaxis mustbe balanced with adverse effects, such as the development of antibiotic-resistant bacteria, approximately two-fold increase ofMDRO, which was not the result of our study.…”
mentioning
confidence: 72%
“…Continual prophylactictreatment in patients with a urinary catheter is strongly discouraged because it maylead to the emergence of resistant bacterial strains [5,6].…”
mentioning
confidence: 99%
“…in pregnancy), clean intermittent self-catheterisation or indwelling catheterisation might be considered as a last resort. The decision for catheterisation should be tailored to patient needs and expectations [46].…”
Section: Catheter Insertionmentioning
confidence: 99%